RF and broadband noise investigation in High‐k/Metal Gate 28‐nm CMOS bulk transistor‡. (6th January 2014) - Danneville, F.; Poulain, L.; Tagro, Y.; Lepilliet, S.; Dormieu, B.; Gloria, D.; Scheer, P.; Dambrine, G.; Crupi, Giovanni; Schreurs, Dominique; Caddemi, Alina
SUMMARY In order to pursue Moore's law, material engineering has constituted a real focus during the last decade. In particular, the recent introduction of new Gate stack using High‐k dielectrics and Metal Gate (H‐k/MG) for CMOS was a key point to downscale the 'Equivalent Oxide Thickness'. Within this context, this paper intends to investigate radio frequency (RF) and broadband noise performance of a recent Low Power 28‐nm H‐k/MG CMOS Bulk Technology. For this purpose, S‐parameters carefully measured up to 110 GHz allowed the selection of the best RF transistor, leading to the best trade‐off for fT/fmax. For this transistor, multi‐bias RF Small Signal Equivalent Circuit (SSEC) was extracted, while its noise performance was assessed through different noise measurement methods and within different frequency ranges. It turned out that H‐k/MG 28‐nm CMOS Technology offers a minimum noise figure NFmin of 0.8 dB (with an associated gain Ga equal to 14 dB) at 20 GHz, for a quite low DC drain current of 135 mA/mm. Moreover, despite the aggressive length down‐scaling, the validity of the two‐temperature noise model was verified both in W band and through tuner based noise measurement in (6–18 GHz) frequency range. Finally, the noise performance were benchmarked with the best ones reported for H‐k/MG CMOS technology up‐to‐date. Copyright © 2014 John Wiley & Sons, Ltd.